MARRIAGE AGREEMENT AS A EFFORT FORMING THE SAKINAH FAMILY - Ach Zakiyuddin (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
Premarital agreements are recognized by Indonesian positive law as binding on both parties, with the Marriage Registry Officer serving as the official witness. Furthermore, the aims of Islamic law and the secrets established by Allah for every Islamic law, including the marriage contract, are called maqasid al-syari ah. It may be inferred that the marriage contract is in compliance with maqasid al-syari ah, based on the study. Because it safeguards the constitutional rights of both the husband and the wife, a marriage contract may aid in the formation of a successful family. It is enough for